Experienciando a ausência do companheiro nas consultas de pré-natal - Silva, Flavio César Bezerra da (2009)
This research aimed to understand pregnant general meaning about consort absence in prenatal care. It s an exploratory and descriptive qualitative approach, developed at Centro de Saúde de Jardim Lola, São Gonçalo do Amarante / RN. Participated in investigation 20 pregnant enrolled in prenatal program, their aged over 18 years, guidance of mental faculties and who survive together her partner. Data were collected from March to May 2009, through semi-structured interview. The analysis was processed according to grounded theory and symbolic interactionism as theoretical and methodological references. To support discussions were used literature findings involving political aspects of women humanization in health care and gender relations within family. Following footsteps of points it were adopted derived following sub categories: ¨Realizing involvement of consort during prenatal¨, ¨Expressing feelings during prenatal¨ and ¨Manifesting attitudes during prenatal period¨. These, when they had their properties and dimensions analyzed, resulted in the main category ¨ Experiencing absence of compeer in clinical prenatal¨. The construction of this theory leads to conclusion that women understand absence of her partner, attributing this to even work at the moment prenatal care or does not like to attend health institutions. However, this does not mean that his presence is dismissed, because desire to be with him in prenatal care was mentioned by most interviewees. So, partner absent at time, leads women to experience desires, feelings, attitudes, perceptions and expectations about studied phenomenon. This reality, induce that absence of them partner in prenatal care predisposes women to strengthening of discomforts arising from pregnancy and therefore goes against wellbeing of pregnant, and ensure the possibility of marital discord. This requires professional nursing measures to get in inclusion of partner in daily pre-natal care in humanization perspective.